Comparison of Caffeine Compound Levels in Brewed and Boiled Oolong Tea Leaves (Camellia sinensis (L.) Kuntze) Based on Different Processing Methods - Styawan, Anita Agustina; Aristhasari Putri; Ocha Ardela Fitria Kresnaya (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2025)
Introduction: Tea contains many compounds that are beneficial for the body, namely caffeine. The process of brewing tea with a time and temperature that is not optimal can affect the caffeine content in it. And the brewing process by heating can widen the distance between the molecules in the tea. The higher the temperature and the longer the brewing time, the higher the caffeine content.. Aims: This study aims to analyze the caffeine content of brewed and boiled oolong tea, then compare the caffeine content of oolong tea with brewing (without heating) and boiled (with heating) processes. Methods: The research method used is experimental. This study used dried samples of oolong tea leaves (Camellia sinensis (L.) Kuntze). Quantitative analysis using UV-Vis Spectrophotometry. Result: Quantitatively, the caffeine content in brewed oolong tea was 3.522% w/w and the caffeine content in boiled oolong tea was 4.001% w/w. The conclusion of this study is that there is no significant difference in caffeine levels in brewed and boiled oolong tea with a significant value of P> 0.05.